Pelatihan penggunaan Zoom Meeting untuk endidikan dan pelatihan di BKPSDM kabupaten Wakatobi - Amin Irmawan (Universitas Hamzanwadi, 2023)
The use of information technology in training has posed a challenge to the sustainability of traditional training methods, be it at a slow or rapid pace. In the post-Covid-19 era, often referred to as the